Efektivitas Model Caring Islami “Praktis” dalam meningkatkan Pengetahuan Perawat - Fajar Yousriatin; Hendra Priyatnanto; Nurul Jamil; Florensa Florensa; Lintang Sari (Universitas Malahayati Lampung, 2024)
ABSTRACT Caring is an attitude that a nurse must have. In Islam, caring is carried out based on Alquran and Sunnah is Islamic Caring as a form of intellectually competent professional behavior from a nurse in providing nursing care to patients, families, and the community with full attention, care, friendliness, empathy, politeness, using communication. therapeutic, and always responsive and alert to provide the best service. This research aims to determine the effectiveness of the